Answer:
An exponential function is in the general form
![\mathrm{y}=\mathrm{a}(\mathrm{b})^{\mathrm{x}}](https://img.qammunity.org/2020/formulas/mathematics/college/l8b57fjrs61k8srvkaead58rxk5g7vdrar.png)
Step-by-step explanation:
(x,y) = (-1,4/3) and (x,y)= (3,108) are the given functions
Therefore,
![(4)/(3)=a(b)^(-1)=(a)/(b)](https://img.qammunity.org/2020/formulas/mathematics/college/c860sew68g7351lo95gweu97tmulajt5un.png)
- eq(1)
![108=a(b)^(3)=a b^(3)=108-e q(2)](https://img.qammunity.org/2020/formulas/mathematics/college/y446wjwa1b2zk2m1iezfaxdyziz85ko4ws.png)
Multiply both sides of the first equation by b to find that
![(4)/(3) b=a](https://img.qammunity.org/2020/formulas/mathematics/college/aehw8pnuxq8cgrfnxax3wrdmz8aktpj6r4.png)
Substituting in eq-2 we get
![(4)/(3) b^(4)=108](https://img.qammunity.org/2020/formulas/mathematics/college/dgkn6buf5pi5sz2ks3gfk8eom1mqpysiam.png)
![b^(4)=81](https://img.qammunity.org/2020/formulas/mathematics/college/cuo3zusa13uqby20zkyxxnpoopojkb85j0.png)
which gives a = 4,
henceforth the equation becomes as
![\mathrm{y}=4(3)^{\mathrm{x}}](https://img.qammunity.org/2020/formulas/mathematics/college/fmjv1d85oviqwk9031tv5caclrla569j1f.png)
![\mathrm{b}=-3 \text { then } 108=\mathrm{a}(-3)^(3)](https://img.qammunity.org/2020/formulas/mathematics/college/u36kojif8qtx0phl2ml0h5ifj4lkz96puc.png)
which gives a = -4,
henceforth the equation becomes as y =
![-4(-3)^(x)](https://img.qammunity.org/2020/formulas/mathematics/college/8fil4n89xte752cu4glp9ylwz6akvnkuks.png)
However! In an exponential function, b>0, otherwise many issues arise when trying to graph the function.
The only valid function is